Development of Composite Floor Tiles of Sand and Recycled Thermoplastics Mixture: A Sustainable Approach for Building Material Production - Khadka, Dak Bahadur; Bhandari , Prajwal; Pakhrin , Samarthak (Journal of the Institute of Engineering, 2023)
Environmental degradation, depletion of natural resources and increase in demand of construction material for the settlement of rapid growth in population has driven the scientific study to find the best alternatives for construction materials. This study aims to provide the idea of sustainability and economy via utilization of non-degradable plastic waste product. The research explores the potential of plastic waste and sand to produce floor tiles as composite construction material. The fabricated floor tiles were tested for water absorption, compression strength, load bearing and drop test to characterize its durability and suitability for paving on non-traffic pavement of public places. The maximum load bearing capacity was found 660KN and compressive strength of 25.4MPA with minimum water absorption of 0.04 and hence found very suitable as paving material in public places for all weather condition. The study recommends the recycledplastic waste as green building material for sustainable development.